Pengembangan Modul Pendidikan dan Pelatihan Materi Perencanaan Perkerasan Jalan pada Perusahaan Jasa Konstruksi - Daniel Jesayanto Jaya; Nuryadin Eko Raharjo (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
The purpose of this research is to develop a Road Pavement Planning Education and Training Module that is suitable to be used as a learning guide in construction service companies as training participants.. The method used is research and development (Research and Development) with the stages of Define (Definition), Design (Designing), Develop (Development) and Disseminate (Spread). The data collection technique uses observation, documentation and questionnaires. The module feasibility validity test was carried out on the instruments outlined in the questionnaire with descriptive data analysis techniques. From the validation results. The material expert stated that the Road Pavement Planning module met the very feasible criteria because it included the competencies needed by training participants with the position of implementing or supervising road works, while the validation of the media expert stated that the module had met the rules of media that was attractive, easy to access, understood so it was very suitable for use by Road Pavement Planning training participants